2006
DOI: 10.1097/01.brs.0000231699.91464.5f
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Magnetic Resonance Imaging Evaluation of Bioresorbable Anterior Cervical Plate Resorption Following Fusion for Degenerative and Traumatic Disk Disruption

Abstract: Based on MRI assessment, these devices, at more than 2-year follow-up, did not indicate any local chronic inflammation or swelling resulting from their degradation. Clinical symptoms of dysphagia or dysarthria, a common reported problem following anterior cervical spine procedures, were not observed in any patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Vaccaro et al [5] reported MRI evaluation of the long-term implant resorption properties of a bioresorbable anterior cervical plate and the adjacent peri-implant soft tissue environment. A retrospective series of patients who underwent a single-level anterior cervical discectomy and fusion followed by anterior plate stabilization using an anterior cervical resorbable mesh plate and screw system (MacroPore Biosurgery) were included in this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccaro et al [5] reported MRI evaluation of the long-term implant resorption properties of a bioresorbable anterior cervical plate and the adjacent peri-implant soft tissue environment. A retrospective series of patients who underwent a single-level anterior cervical discectomy and fusion followed by anterior plate stabilization using an anterior cervical resorbable mesh plate and screw system (MacroPore Biosurgery) were included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the complications associated with the material used, Vaccaro et al [5] found that the prevertebral space (used as an indicator of soft tissue reaction derived from cervical fixation with absorbable plates) was on average 20 mm immediately after implantation, then recovering to 13 mm during the follow-up. He found no clinical translation of this inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abweichungen von dieser Sicht sind selten. Die Cages sollen, mit oder ohne Plattenabstützung, auch in diesem Sinne wirken [1,2,3,4,18,22,23,29,30,33,39,50,52,57,60,62].…”
Section: Knochentransplantat/ Knochenersatzstoffunclassified
“…Es wurden immer neuere Plattensysteme entwickelt und es wurde nach dem besten Span gesucht. Deutlich wenig Aufmerksamkeit wurde dagegen der Sicherheit und der Schnelligkeit des biologischen Einbaus des Knochentransplantates geschenkt [1,2,3,4,13,16,18,22,23,29,33,38,39,42,50,52,57,62].…”
unclassified